Comparison of Ocular Ultrasonography and Magnetic Resonance Imaging for Detection of Increased Intracranial Pressure - Patterson, David F.; Ho, Mai-Lan; Leavitt, Jacqueline A.; Smischney, Nathan J.; Hocker, Sara E.; Wijdicks, Eelco F.; Hodge, David O.; Chen, John Jing-Wei (Frontiers in Neurology, 2018)
Background/aims To evaluate and compare the performance of ocular ultrasonography (US) and magnetic resonance imaging (MRI) for detecting increased intracranial pressure (ICP) in patients with idiopathic intracranial hypertension (IIH). Methods Twenty-two patients with papilledema from IIH and 22 with pseudopapilledema were prospectively recruited based on funduscopic and clinical findings. Measurements of optic nerve sheath diameters (ONSDs) 3 mm behind the inner sclera were performed on B-scan US and axial T2-weighted MRI examinations. Pituitary-to-sella height ratio (pit/sella) was also calculated from sagittal T1-weighted MRI images. Lumbar puncture was performed in all patients with IIH and in five patients with pseudopapilledema. Results Average US and MRI ONSD were 4.4 (SD ± 0.7) and 5.2 ± 1.4 mm for the pseudopapilledema group and 5.2 ± 0.6 and 7.2 ± 1.6 mm for the papilledema group (p < 0.001). Average MRI pit/sella ratio was 0.7 ± 0.3 for the pseudopapilledema group and 0.3 ± 0.2 for the papilledema group (p < 0.001). Based on receiver-operator curve analysis, the optimal thresholds for detecting papilledema are US ONSD > 4.8 mm, MRI ONSD > 6.0 mm, and MRI pit/sella < 0.5. Combining a dilated US ONSD or MRI ONSD with a below-threshold MRI pit/sella ratio yielded a sensitivity of 73% and specificity of 96% for detecting IIH. Adding the US ONSD to the MRI ONSD and pit/sella ratio only increased the sensitivity by 5% and did not change specificity. Conclusion US and MRI provide measurements of ONSD that are well-correlated and sensitive markers for increased ICP. The combination of the ONSD and the pit/sella ratio can increase specificity for the diagnosis of IIH.